A Study on Saving, Investment Pattern and Financial Awareness of Youth in Bangalore City - Dr Rajdeep Manwani, Raghappanavara Dharmaraj Prakasha; Shruthi Joshi, Rajendra A V (Journal of Informatics Education and Research, 2025)
The women in Indian families have the habit of saving a little portion of the household expenses, provided to them, by the family head. The women in India are earning a substantial income, to complement the earnings of their family and also spend a portion of their earning towards household expenses. Apart from taking care of their personal and other entertainment expenses, the primary purpose of earning by women is to save for future security or unpredictable future contingencies. The faculty members, working in private universities, are underpaid when compared to the faculty members working in government institutions and hence they have to be extra cautious while making their investment in various investment avenues. This study is to analyze the effect of investment in various investment avenues, The respondents reported a very good level of awareness on the investment avenues like bank fixed deposit, gold, post office, insurance policies, and provident fund.